IT Infrastructure Role in the Success of a Banking System: The Case of Limited Broadband Access. Issue 2 (2nd April 2016) - Borena, Berhanu; Negash, Solomon
Abstract : This study provides empirical support for including IT infrastructure (ITI) as part of the information systems (IS) success model. The IS success model has been validated in high-income countries, but research in low-income countries is still lacking. This research bridges this gab by identifying ITI as a contributing construct when evaluating the IS success model in the context of low-income countries. This paper investigates the research question: when considering low-income countries, what is the role of ITI in information systems success? The research is motivated by limited ITI and limited Internet access in low-income countries that hinder the success of information systems. We conducted a survey with 102 bank employees in a low-income country – Ethiopia. The SEM-PLS analysis showed strong impact of ITI on user, user satisfaction, and net benefit. This study recommends inclusion of the ITI construct when evaluating the success of information systems and the policies that govern it.